Peran Sosial Media Instagram Dalam Membantu Kegiatan Promosi Perpustakaan di Perpustakaan Universitas Islam Negeri Sumatera Utara - Elgy Wijayanti; Annisya Annisya; Nurul Aini; Sarida Sinulingga; Kartini Kartini (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Library Promotion currently holds custodial (minor) positions in Information Science and Library Education at various universities in Indonesia. So don't be surprised if the production unit, which is then called the library, stagnates and stops working. Developing a blog-based library expands the possibilities of your user base, but using a freeware database is sufficient to become the backbone of your library automation. In the current Development 4.0 era, library promotion through Instagram social media is considered more effective and efficient. Interaction between librarians and users can now take place virtually by utilizing existing information technology. The researchers looked specifically at one account of university libraries: universities. Communicating with users via Instagram is an effective way to advertise in university libraries. This article also describes the forms of interaction provided by the Instagram application and how the UIN North Sumatra Library itself uses the facilities available on Instagram. The data collection method consisted of observing the Instagram account of the North Sumatra State Islamic University Library and conducting a literature review. The results of a survey conducted by the UIN Sumut library utilized all existing facilities on Instagram to promote the library. Libraries use the Instagram Stories feature to upload videos and photos, as well as Instagram Direct to promote their library. Keywords: Library promotion, Social media, Instagram